MENGGUNAKAN PERSPEKTIF POST- DEVELOPMENTALISME: BERNYANYI DI PENDIDIKAN ANAK USIA DINI - Suci Ramdaeni (Equalita: Jurnal Studi Gender dan Anak, 2021)
This study aims to explore gender constructs in early childhood education. Through a post-developmentalism perspective, this research uncovers how masculine and feminine binaries reinforce inequality in PAUD. This study uses a meta-analysis research method that integrates previous research through a post-developmentalism perspective. The findings of this study indicate that children often reinforce inequality through understanding gender stereotypes, choosing the type of song, and selecting the song instrument that is constructed in early childhood education. It is hoped that this research will become a reflection for teachers and adults to be more gender sensitive. So that boys and girls get the same stimulation and experience in singing in PAUD.in the form of stimulation and the same experience in singing to boys and girls